Association of Risk Factors with Type 2 Diabetes: A Scoping Review - Hulu, Victor Trismanjaya; Saragih, Julwansa; Damanik, Balqis Nurmauli; Damanik, Derma Wani; Yunia, Eva Anita; Sinurat, Buenita (Universitas Prima Indonesia, 2024)
The incidence of type 2 diabetes mellitus (type 2 DM) is one of the public health problems worldwide, with various factors as risk factors that can lead to high morbidity and mortality rates for people with type 2 DM. This study aims to identify, investigate, and summarize various scientific evidence related to risk factors for type 2 DM. The approach used in this study was a scoping review with the PRISMA protocol. The PICO framework was used as an early-stage strategy in conducting article searches. Databases such as Google Scholar, PubMed, Scopus, and ScienceDirect were used as literature search tools. The study inclusion criteria were journal articles published from 2016 to 2024 and English-language articles with open access. Of the 157 journal articles identified, only 11 were eligible for analysis after selection and eligibility. The data extraction stage was conducted by six people on 11 eligible articles and continued with the qualitative data analysis process. The study reported that age, education, duration of DM, gender and income, physical activity, obesity, consumption of sugary foods and beverages, and low fruit consumption are risk factors for type 2 DM.